Sleep Quality among Adolescents of Three Districts of Central Kerala - Joy, Joyalyn; Abraham, Anju; Jose, Anna Maria; Manoj, Bhagia Anna; Jetto, Dona Maria; George, Shaji (Indian Journal of Pharmacy Practice)
Background: Sleep is a vital human need that must be satisfied in a sufficient quantity and in a suitable quality. Because of the possible effects on memory reorganization, learning, decision-making, critical thinking, academic achievement, social conduct, and the cardio metabolic system, adolescent sleep patterns deserve special consideration. Objectives: To Assess the quality and pattern of sleep among adolescents. Materials and Methods: The study included 604 adolescents aged 10 to 18 carried out in three districts of central Kerala. Students were given a questionnaire that included PSQI scale items as well as demographic information. Seven components such as subjective sleep quality, sleep latency, sleep duration, habitual sleep efficiency, sleep disturbances, use of sleeping medications, and daytime dysfunction were the major parameters assessed. Results: The group as a whole had a mean age of 14.4 years (SD: 0.40). The male students participated in this study were 307 (50.8%) and female students 297 (49.1%). Stressful life situations occurred for 90 (14.9%) students, of which 37 (6.1%) male and 53 (8.7%) female students. 126 students (20.8%) reported presence of medical condition among which 61 (10.1%) were males and 65 (10.7%) were females. Students who had stressful life events 36 (39.56%) and those who had medical issues 36 (28.57%) were shown to have lower sleep quality. Sleep disturbances were reported higher in students with stressful life events 2 (2.19%) and medical condition 2 (1.58%). Students with medical conditions reported a higher percentage of stressful life events 20 (21.97%). Conclusion: Majority of adolescents has good quality sleep and a few are facing sleep related difficulties.
Keywords: Sleep latency; Stressful life events; Sleep duration; Daytime dysfunction; Sleep disturbances.